Penang travel service provider application using geofencing / Nurezzatul Husna Ismail and Mohd Nizam Osman - Ismail, Nurezzatul Husna; Osman, Mohd Nizam (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Penang Travel Service Provider Application is a tourism application that is developed to ease the work of travelers or backpackers. This mobile application is integrated with geofencing technology that enables users or travelers to detect attractions around them in specific areas. Alongside with the technology integrated, this mobile application has a few functionality such as enabling users to book a hotel, make vehicle reservation, buying ticket through a directed link to its own website also consist of an information booth inside the application which makes it a multifunctional mobile app. This application is being developed based on Android platform as the operational system which requires Android developing software which is Android Studio. Firebase also has been used. The development of this mobile application has been done using Agile as its methodology. A total of 30 respondents from Penang conducted a user acceptance test using a questionnaire. While another 10 respondents also in the same group had been conducted an interview. Results of evaluation have found that almost all respondents are satisfied with the criteria of the mobile application included in. Therefore, this mobile application could be helpful for travelers and backpackers who plan to travel to Penang as its functionality and features would give benefits to them.